MIGRATION AND RECURRENCE OF GREAT EARTHQUAKES IN KAMCHATKA AND THE NORTHERN KURILS - Vikulin A.V. (My University, 1993)
The Benioff zone off Kamchatka and the northern Kuril Islands is divided into several blocks using the source area locations of great 20th century earthquakes. The occurrence of the great 18 to 20th century earthquakes defines three migrations. Two of them take place along the Benioff zone. One involves several blocks, or source areas of great earthquakes, and is from southwest to northeast, the duration of earthquake sequences being within 21 years. The other involves all blocks and proceeds in both directions at approximately equal velocities, 4±1 km/yr. Some evidence suggests that the source areas of great events migrate across the Benioff zone, the mean recurrence time being 100±40 years. The results obtained will be used to forecast the periods of time during which great earthquakes are likely to occur within the blocks.
Keywords: 37.31.19 Сейсмология